Identification of microclimate in jajar legowo planting system and its effect on brown plant hopper and Lycosa sp. - Saputra Fajar Eka; Supriyadi; Muliawati Endang Setia (E3S Web of Conferences, 2023)
Rice was an important food crop that one of the cultivation was the jajar legowo planting system. However, the effect of the planting system on brown planthopper and predatory Lycosa has not been well studied, related to microclimate changes. This study aims to identify microclimate factors in the jajar legowo and their effects on brown leafhopper populations and Lycosa. This research was designed through field experiments in rice fields with the treatment of legowo planting system (2: 1) and conventional system as a check. The research variables consisted of temperature, humidity, light intensity, brown leafhopper population, and Lycosa population. The results of this study showed the highest humidity was at the end of the planting period. The temperature and light intensity recorded in jajar legowo planting systems tends higher. The population of Lycosa in the Jajar legowo planting system was highest in the 2 week after transplanting (WAT), while in the conventional planting, the system was found in the 1 WAT The highest brown plant hopper population was recorded at 3 WAT, while in jajar legowo at 2 WAT. The results of this study showed no significant effect of microclimate factors on the Lycosa population and brown leafhopper populations. The benefit of this research is knowing the effect of microclimate on lycosa and WBC populations in Jajar Legowo and Conventional rice planting systems.